Achieving rural spatial restructuring in China: A suitable framework to understand how structural transitions in rural residential land differ across peri-urban interface?. (June 2018) - Ma, Wenqiu; Jiang, Guanghui; Zhang, Ruijuan; Li, Yuling; Jiang, Xiaoguang
Highlights: Rural residential land transition is always embodied in its internal structure. There are three transition patterns in China, i.e., non-agriculture, rurality and decay. Urbanization changed the land use structure through the population flow. Industrialization shaped the RLST through shaping village industrial structure. Multifunctionality of rural land use should be encouraged in rural spatial restructuring. Abstract: Since the late twentieth century, rural areas in China have experienced a rapid and far-reaching transformation of social and economic structures. Residential land in rural areas, as a type of land where rural residents live and engage in producing, is under significant pressure and face significant change as a consequence. How has rural residential land changed over time, and why it differs across peri-urban interface? This paper presents a methodology for confronting this issue. By applying an integrated framework, we explored the rural residential land transition patterns from the internal structure, i.e., rural residential land-use structural transition (RLST) and identified the driving forces from the perspective of urbanization and industrialization. Our findings show that there are three RLST patterns in China, i.e., non-agriculture, rurality and decay. During the period, the peri-urban area – Pinggu has shown the coexistence of non-agriculture and decay patterns. In particular, RLST patterns varied at different levels. Spatially, along with getting closer to urban areas came increasing complexity of RLST patterns, which formed the structure of circle layer. The various RLST patterns are closely linked to interaction and reorganization between external and internal factors, including basic condition, industrialization, urbanization and policies. Among of them, urbanization changed the internal structure of rural residential land through the population flow; while industrialization influenced the RLST through shaping the industrial structure and level of economic development. Other outstanding issues discussed in this paper relate to the implication for rural spatial restructuring and benign rural residential land transition, which can be achieved through industrial structure reshaping, population relocation and cultural regression. The findings of this study can help us better understand the process of rural residential land transition and thus have significance for the land use multifunctionality and restructuring policies in rural China.